AGRICULTURAL COOPERATIVES AND RURAL DEVELOPMENT - Šljukić, Srđan (Economics of Agriculture, 2007)
In this paper the author firstly talks about numerous prejudices that still exist about cooperatives. The source of these prejudices is the historical period in which the state fully controlled cooperative movement, compromising and impeding it. A cooperative, including an agricultural cooperative, is an institution of a modern society, by which social actor are trying to increase their power at the market. Agricultural cooperatives exist among farmers both the in the USA and in the EU. Each society has been trying to increase its power, which can be seen, besides other forms, as a quantity of resources that a society possesses. These resources can be called economic, cultural and social capital. Agricultural cooperatives represent a lever of rural development, i.e. one of the institutions that can be used to increase economic, cultural and social capital in an area. The influence of agricultural cooperatives to employment has two forms: first, they stimulate self-employment (those who want to engage themselves in agricultural production know they can join or establish an organization); second, when agricultural cooperatives invest in industrial plants, the demand for hired labor increases.